Surviving murine experimental sepsis affects the function and morphology of the inner ear - Natalie Fischer; Nina Maria Mathonia; Georges Hoellerich; Julian Veser; Leyla Pinggera; Daniel Dejaco; Rudolf Glueckert; Anneliese Schrott-Fischer; Peter Lackner; Herbert Riechelmann; Joachim Schmutzhard (Biology Open, 2017)
Severe sepsis is known to result in various neurological long-term deficits in human. Recently, a link between severe, lethal sepsis and significant hearing loss with correlating histomorphological inner ear changes in mice (C57BL/6) was observed. However, if similar observations can be made in severe, non-lethal sepsis in mice is unclear. This study evaluates mice after severe, non-lethal sepsis for analogue functional and histomorphological alterations of the inner ear. A total of 63 C57BL/6 mice were included in the study. All underwent an initial hearing test with auditory brainstem response on day 1. In 35 mice sepsis was induced by cecal ligation and puncture (CLP), in 15 sham surgery was performed and 13 served as healthy control. A second hearing test was performed on day 7. All mice were sacrificed afterwards for further histomorphological evaluation of the inner ears. Immunohistochemical analysis with apoptotic markers Cleaved-caspase 3, BAX and BCL-2 were performed to identify structural inner ear damage. Of all CLP mice, 21/35 (60.0%) died due to the induced sepsis. Of the surviving CLP mice, 14/35 (40.0%), post-treatment hearing thresholds differed significantly from the sham and control mice (P<0.001). Positive immunostaining at different inner ear structures, like the spiral ligament or the supporting cells could be observed. The percentage of the immunostained positive area in the spiral ligament significantly correlated with the grade of hearing loss for BAX (P=0.027) and Cleaved-caspase 3 (P=0.024) but not for BCL 2 (P>0.05). The present data suggests that severe, non-lethal sepsis in mice results in significantly elevated hearing thresholds. A positive labelling for the pro-apoptotic markers BAX and Cleaved-caspase 3 suggested the induction of apoptosis in inner ear.